Modulation of recurrent inhibition from knee extensors to ankle motoneurones during human walking - Lamy, Jean-Charles (Blackwell Science Inc, 2008)
The neural control for muscle coordination during human locomotion involves spinal and supraspinal networks, but little is known about the exact mechanisms implicated. The present study focused on modulation of heteronymous recurrent inhibition from knee extensors to ankle motoneurones at different times in the gait cycle, when quadriceps (Quad) muscle activity overlaps that in tibialis anterior (TA) and soleus (Sol). The effects of femoral nerve stimulation on ankle motoneurones were investigated during treadmill walking and during tonic co-contraction of Quad and TA/Sol while standing. Recurrent inhibition of TA motoneurones depended on the level of background EMG, and was similar during walking and standing for matched background EMG levels. On the other hand, recurrent inhibition in Sol was reduced in early stance, with respect to standing, and enhanced in late stance. Reduced inhibition in Sol was also observed when Quad was coactivated with TA around the time of heel contact, compared to standing at matched background EMG levels in the two muscles. The modulation of recurrent inhibition of Sol during walking might reflect central and/or peripheral control of the Renshaw cells. These modulations could be implicated in the transition phases, from swing to stance to assist Sol activation during the stance phase, and from stance to swing, for its deactivation.